Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/jcb.28090
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy by lentivirus‐mediated RNA interference targeting extracellular‐regulated kinase alleviates neuropathic pain in vivo

Abstract: Backgrounds Neuropathic pain is an abnormal pain, which is related to the activation of extracellular‐regulated kinase (ERK) signaling. This study was to investigate the effects of ERK knockdown via lentivirus‐mediated RNA interference on allodynia in rats with chronic compression of the dorsal root ganglia (DRG) and to uncover the potential mechanisms. Methods The model of chronic compression of the dorsal root ganglia (CCD) was established in rats by surgery. Gene silence was induced by injecting rats with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…There are not enough studies on obesity-induced neuropathic pain, and therefore the precise mechanism is still not fully elucidated, and the effective clinical treatments are lacking. Our previous studies have confirmed that MAPK/ERK contributes to CCD-induced neuropathic pain, and inhibition of ERK phosphorylation with U0126 and interference of ERK expression with shRNA can alleviate pain [ 8 , 9 ]. Combined with previous studies showing that in smooth muscle cells and adipocytes, treatment with lipids can lead to ERK activation [ 10 , 11 ], we hypothesized that the elevated neuropathic pain in obese rats might be related to the abnormal activation of ERK in nervous tissue.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…There are not enough studies on obesity-induced neuropathic pain, and therefore the precise mechanism is still not fully elucidated, and the effective clinical treatments are lacking. Our previous studies have confirmed that MAPK/ERK contributes to CCD-induced neuropathic pain, and inhibition of ERK phosphorylation with U0126 and interference of ERK expression with shRNA can alleviate pain [ 8 , 9 ]. Combined with previous studies showing that in smooth muscle cells and adipocytes, treatment with lipids can lead to ERK activation [ 10 , 11 ], we hypothesized that the elevated neuropathic pain in obese rats might be related to the abnormal activation of ERK in nervous tissue.…”
Section: Discussionmentioning
confidence: 94%
“…The test method is based on our previous reports [ 8 ]. The rats were fully accustomed to the test environment before the test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CCD was induced as described earlier (Jia et al, 2018). In summary, after the rats were anesthetized, the paraspinal muscles were separated to unilaterally expose the transverse processes and intervertebral foramina of L4 and L5.…”
Section: Ccd Modelmentioning
confidence: 99%
“…Thermal paw withdrawal latency (TPWL) was measured using the BME-410C thermal analgesia tester (CAMS) as described previously (Jia et al, 2018). The light source was a 12 V/10 W halogen lamp and the thermal intensity was set at 60 • C. Radiant light was focused on the center of the hind paw at about 1 cm, and TPWL was recorded when the rat lifted or licked the hind paw.…”
Section: Nociceptive Behavioral Testingmentioning
confidence: 99%